2017
DOI: 10.1088/1361-6463/aa8798
|View full text |Cite
|
Sign up to set email alerts
|

Influence of residual stress on the adhesion and surface morphology of PECVD-coated polypropylene

Abstract: The properties of plasma-enhanced chemical vapour deposition (PECVD) coatings on polymer materials depend to some extent on the surface and material properties of the substrate. Here, isotactic polypropylene (PP) substrates are coated with silicon oxide (SiOx) films. Plasmas for the deposition of SiOx are energetic and oxidative due to the high amount of oxygen in the gas mixture. Residual stress measurements using single Si cantilever stress sensors showed that these coatings contain high compressive stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Further descriptions of duo plasma lines and the utilized reactor are found elsewhere. [ 6,11,12 ] The parameters for coating deposition are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further descriptions of duo plasma lines and the utilized reactor are found elsewhere. [ 6,11,12 ] The parameters for coating deposition are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The parameters were selected on the basis of the investigations from Jaritz et al, [ 12 ] because it was already shown that by means of the SiO x parameter barrier coatings, and by means of the SiOCH/SiNOCH parameters, less cross‐linked adhesion promoter layers can be produced in this reactor. Furthermore, it was shown in this article that the duty cycle has a direct influence on the degree of cross‐linking and the generation of intrinsic stresses in HMDSO‐based coatings.…”
Section: Methodsmentioning
confidence: 99%
“…One primary method that was used to quantify residual stresses on a polymer flat sheet consists of measuring the curvature of the samples before and after applying the deformation mechanical or thermal load . Once the sample is free of constraints, it restores equilibrium by warping to a shape that resembles somewhat a circular arc …”
Section: Methodsmentioning
confidence: 99%
“…For a number of applications of organic electronics, the WVTR and OTR targets for semi-hermetic packaging are 10 –6 g m –2 day –1 and 10 –3 g m –2 day –1 atm –1 , respectively. The upper-limit requirements of WVTR and OTR for organic electronics are about 6–8 orders of magnitude lower than the corresponding values of commercially available polymer films, whereas improvement by 1–3 orders of magnitude is considered sufficient for applications in food and pharmaceutical packaging . To address this shortcoming, ultrathin barrier films consisting of inorganic brittle materials are deposited on organic substrates as barrier layers to protect the functional layer of the device from oxygen and moisture permeation. Vacuum deposition methods such as PECVD, ALD, etc., are often used to create the ultrabarrier films, , and current ultrathin barrier film technology has reached an effective WVTR on the order of 10 –4 –10 –6 g m –2 day –1 . …”
Section: Introductionmentioning
confidence: 99%